The Role Of Digital Media In Improving Students' English Speaking Skills At STAI Ma'arif Sampang - Khoirul Anam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Improving English speaking skills is one of the important aspects in language education, especially for students at The State of Islmic Collage (STAI Ma'arif) Sampang who are preparing to communicate in a global context. In this digital era, digital media offers a new approach that allows students to learn flexibly, listen to native languages, and practice independently. This study was conducted to understand the extent to what digital media have a role in improving students' English speaking skills at The State of Islmic Collage (STAI Ma'arif) Sampang, the types of media most often used, and the supporting and inhibiting factors that affect its effectiveness. This research uses a qualitative approach with a case study design to explore students' experiences and perceptions of the use of digital media in learning to speak. Data were obtained through in depth interview and observation to students who frequently use language learning apps and online communication platforms. The purposive sampling technique was chosen to ensure participants had relevant first-hand experience, while thematic analysis was used to identify patterns and themes from the data collected. The results show that digital media plays a significant role in supporting students'. English speaking skills. Platforms such as YouTube, Zoom and language learning apps provide authentic materials and flexible in speaking spaces practice, which help students to improve vocabulary, pronunciation and their confidence. However, the research also found that there are inhibiting factors, such as limited internet access and lack of direct guidance from instructors, which can affect students' consistency in utilizing digital media.